2009
DOI: 10.3329/jbsa.v18i1.4031
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive Analgesia for Postoperative Pain Relief in Children – Role of Paracetamol

Abstract: and than (318± 26.39). Total duration of analgesia in mins. Pre-emptive high dose rectal paracetamol appears to be more effective than diclofenac sodium suppository for postoperative analgesia in children undergoing tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The use preemptive analgesia to reduce analgesic requirements and adverse drug reactions, is not new and increasingly have been studied with the techniques and drugs that take advantage of this property, where our group studies (paracetamol and ketorolac) have already been reviewed previously having enough satisfactory results [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The use preemptive analgesia to reduce analgesic requirements and adverse drug reactions, is not new and increasingly have been studied with the techniques and drugs that take advantage of this property, where our group studies (paracetamol and ketorolac) have already been reviewed previously having enough satisfactory results [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal preemptive analgesia using IV ketorolac and bupivacaine infiltration was found to be very effective to control postoperative pain in maxillofacial surgeries 20 . Another study has shown that high dose per-rectal paracetamol as preemptive analgesia was more effective than per-rectal Diclofenac sodium in children 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Sosyo Demografik Bilgi Formu; İlgili literatür doğrultusunda (11,12,14) araştırmacılar tarafından hazırlanmıştır. Çocuğun yaşı, cinsiyeti, tıbbi tanısı, geçmişteki ve mevcut sağlık durumu, daha önce ameliyat geçirip geçirmediği, kullandığı ilaçlar, geçmiş tıbbi öyküsü, geçmiş ağrı deneyimi, ameliyat sırasında aldığı anestezinin türü, ameliyat sonrası analjezi alıp almaması, aldıysa bu analjezik ilacın veriliş yolu ve türünü tanılamaya yönelik sorulardan oluşmaktadır.…”
Section: Veri Toplama Araçlarıunclassified